2017
DOI: 10.1007/s10584-017-2076-z
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Indigenous peoples in climate change reporting

Abstract: This article examines how newspapers reporting on climate change have covered and framed Indigenous peoples. Focusing on eight newspapers in Canada, the USA, Australia, and New Zealand, we examine articles published from 1995 to 2015, and analyze them using content and framing analyses. The impacts of climate change are portrayed as having severe ecological, sociocultural, and health/safety impacts for Indigenous peoples, who are often framed as victims and Bharbingers^of climate change. There is a strong focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 40 publications
4
41
1
2
Order By: Relevance
“…2 (Climat* Change* OR Global Warming* OR Greenhouse Effect*) AND (Pacific Island* OR Pacific atoll* OR Melanesia* OR Polynesia* OR Cook Islands* OR Micronesia* OR Fiji* OR Kiribati* OR Vanuatu* OR Marshall Islands* OR Tuvalu* OR Nauru* OR Niue* OR Palau* OR Papua New Guinea* OR Samoa* OR Solomon Islands* OR Tonga*) 3 This time period was constrained by the lack of archived articles in Factiva for several of the study newspapers before 1999, but coverage of Pacific Islands and climate change in available newspapers before 1999 was also sparse. The two-decade time period is also consistent with other long-term MCCC studies (Belfer et al 2017;Ford and King 2015) that did not still fell in the good strength of agreement range (κ > .6) based on the guidelines from Altman (1991). Statistical analyses were performed on coding data using SPSS.…”
Section: Codingsupporting
confidence: 78%
See 1 more Smart Citation
“…2 (Climat* Change* OR Global Warming* OR Greenhouse Effect*) AND (Pacific Island* OR Pacific atoll* OR Melanesia* OR Polynesia* OR Cook Islands* OR Micronesia* OR Fiji* OR Kiribati* OR Vanuatu* OR Marshall Islands* OR Tuvalu* OR Nauru* OR Niue* OR Palau* OR Papua New Guinea* OR Samoa* OR Solomon Islands* OR Tonga*) 3 This time period was constrained by the lack of archived articles in Factiva for several of the study newspapers before 1999, but coverage of Pacific Islands and climate change in available newspapers before 1999 was also sparse. The two-decade time period is also consistent with other long-term MCCC studies (Belfer et al 2017;Ford and King 2015) that did not still fell in the good strength of agreement range (κ > .6) based on the guidelines from Altman (1991). Statistical analyses were performed on coding data using SPSS.…”
Section: Codingsupporting
confidence: 78%
“…A discourse analysis of articles about Tuvalu in The Sydney Morning Herald found that Tuvaluan identity was often constructed in opposition to Australian stability and in connection to Tuvalu's physical vulnerability (Farbotko 2005). More broadly, analysis of newspaper articles about Indigenous peoples and climate change found a similar tendency to portray Indigenous peoples as victims (Belfer et al 2017). To expand on this scholarship, we aim to assess the relative presence of different narratives in reporting on Pacific Islands and climate change (RQ2).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the awareness of soil erosion and its impacts has positively influenced the adoption of AMs within the local agriculture. This is consistent with the numerous earlier studies regarding the interplay between local perception and AMs in agricultural techniques not only in Vietnam [21,34], but also such countries as Tanzania [96], Thailand [97], Canada, the USA, Australia, and New Zealand [98]. Our findings indicated that most of the farmers are already adapting quite extensively to these new environmental concerns by using their innate instinctual capacity to implement cultural initiatives.…”
Section: From Perception To Adaptive Measures Regarding the Soil Erossupporting
confidence: 92%
“… Acknowledgement of the roles of colonialism, marginalization, and Indigenous histories in shaping both traditional ecological knowledge (TEK) and how societies respond to climate threats (Belfer, Ford, & Maillet, ) …”
Section: Analytical Approachmentioning
confidence: 99%